Permeability coefficient and porosity characteristics of bagasse fiber reinforced concrete (2013)
The durability of concrete structures is a major challenge facing concrete community today. Porosity and permeability played paramount roles in determining the durability of concrete. The inclusion of fibre reinforcement in concrete can enhance some of its engineering properties. This paper investigated the influence of bagasse fibre inclusion on the porosity and permeability of concrete. A series of laboratory porosity and permeability tests were carried out. The fibre length varied from 10mm to 25mm while the volume ranged from 0 to 5% of cement mass. The results proved that bagasse fibre inclusion increased the porosity and reduced the permeability slightly initially and increased it afterwards. At fibre volume of less than 3%, the influence of different lengths of fibre on water permeability shows that high porosity does not mean high permeability. The main factor which governs permeability is the void spaces interconnections.